2021
DOI: 10.15452/cejnm.2021.12.0016
|View full text |Cite
|
Sign up to set email alerts
|

Dignity of patients with multiple sclerosis: a qualitative descriptive study

Abstract: Aim:The aim of the study was to identify the impact of multiple sclerosis (MS) on the dignity of patients. Design: A qualitative descriptive design. Methods: Semi-structured interviews with eight participants were used to collect empirical data. The mean age of participants was 50 years. On average, participants were 21.9 years after diagnosis. A thematic analysis was used to analyze the data. Results: 21 sub-themes emerged from thematic analysis, which were grouped into four interconnected themes: Identity ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…This ability may result from inner creativity, helping residents to remain self-dependent, even if their bodies fail [ 53 ]. Residents in this study appeared to have found dignity by accepting disease and deterioration with a fighting spirit, which aligns with research with younger people with multiple sclerosis [ 54 ].…”
Section: Discussionsupporting
confidence: 79%
“…This ability may result from inner creativity, helping residents to remain self-dependent, even if their bodies fail [ 53 ]. Residents in this study appeared to have found dignity by accepting disease and deterioration with a fighting spirit, which aligns with research with younger people with multiple sclerosis [ 54 ].…”
Section: Discussionsupporting
confidence: 79%
“…This ability may result from an inner creativity, helping residents to remain self-dependent, even as their bodies fail [50]. In compliance with research performed on younger people with multiple sclerosis, residents in this study appeared to have found dignity by accepting disease and deterioration with a ghting spirit [51]. Further, the residents of this study took pride in what they had achieved and what they could still do.…”
Section: Discussionsupporting
confidence: 71%
“…However, dignity is embraced by most national and international human rights frameworks ( Chapman et al, 2022a ). Researchers have attempted to resolve these criticisms by considering the meaning of dignity as it applies to a particular practice such as palliative care ( Chochinov 2002 , 2007 ), dementia services ( Kracmarova et al, 2022 ), and healthcare ( Frounfelker & Bartone, 2021 ; Lind et al, 2014 ; Philipp et al, 2016 ; Podolinska & Cap, 2021 ). Although these examinations include lists of the barriers and enablers to dignity in individual contexts, little is known about how dignity is understood, defined, and experienced by marginalised populations, particularly people with disability ( Lohne et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%